Impact of HDAC Inhibitors on Protein Quality Control Systems: Consequences for Precision Medicine in Malignant Disease - Kulka, Linda Anna Michelle; Fangmann, Pia-Victoria; Panfilova, Diana; Olzscha, Heidi (Frontiers in Cell and Developmental Biology, 2020)
Lysine acetylation is one of the major posttranslational modifications (PTM) in human cells and thus needs to be tightly regulated by the writers of this process, the histone acetyl transferases (HAT), and the erasers, the histone deacetylases (HDAC). Acetylation plays a crucial role in cell signaling, cell cycle control and in epigenetic regulation of gene expression. Bromodomain (BRD)-containing proteins are readers of the acetylation mark, enabling them to transduce the modification signal. HDAC inhibitors (HDACi) have been proven to be efficient in hematologic malignancies with four of them being approved by the FDA. However, the mechanisms by which HDACi exert their cytotoxicity are only partly resolved. It is likely that HDACi alter the acetylation pattern of cytoplasmic proteins, contributing to their anti-cancer potential. Recently, it has been demonstrated that various protein quality control (PQC) systems are involved in recognizing the altered acetylation pattern upon HDACi treatment. In particular, molecular chaperones, the ubiquitin proteasome system (UPS) and autophagy are able to sense the structurally changed proteins, providing additional targets. Recent clinical studies of novel HDACi have proven that proteins of the UPS may serve as biomarkers for stratifying patient groups under HDACi regimes. In addition, members of the PQC systems have been shown to modify the epigenetic readout of HDACi treated cells and alter proteostasis in the nucleus, thus contributing to changing gene expression profiles. BRD-containing proteins seem to play a potent role in transducing the signaling process initiating apoptosis, and many clinical trials are under way to test BRD inhibitors. Finally, it has been demonstrated that HDACi treatment leads to protein misfolding and aggregation, which may explain the effect of panobinostat, the latest FDA approved HDACi, in combination with the proteasome inhibitor bortezomib in multiple myeloma. Therefore, proteins of these PQC systems provide valuable targets for precision medicine in cancer. In this review, we give an overview of the impact of HDACi treatment on PQC systems and their implications for malignant disease. We exemplify the development of novel HDACi and how affected proteins belonging to PQC can be used to determine molecular signatures and utilized in precision medicine.